SPEED CONTROL OF PMSG SUPPLIED CLOSED LOOP PMSM DRIVE FOR WATER PUMPING SYSTEM - RAHOUA, NAIMA; ABDESSEMED, RACHID (Courrier du Savoir, 2018)
This paper introduces a standalone variable speed wind energy conversion system(WECS) based on permanent magnet synchronous Generator (PMSG) supplied permanent magnet synchronous Motor (PMSM) drive for water pumping system. Pumping water is a worldwide   need that is necessary for agriculture and the usage of wind energy conversion is a choice that is considered natural for that kind of applications. The Permanent magnet synchronous motor (PMSM) drive that is powered by high speed wind energy conversion system is investigated. The WECS application is inquired, in order to high light the wind speed effect on the WECS feeding the PMSM, where the speed of a PMSM drive is a function of wind speed. The proposed system consists of  WECS using PMSG, a rectifier converter, a three phase VSI (Voltage Source Inverter) and a PMSM coupled with a centrifugal water pump. The suggested control strategies are focused on Maximum Power Point Tracking (MPPT) for PMSG speed control, and DC-bus voltage management. Three phase VSI (Voltage Source Inverter) is also controlled to supply PMSM under change in wind speed in vector oriented mode. Some simulations are done using Matlab / Simulink software in order to show the control strategies performances.